PERTUMBUHAN DAN PERKEMBANGAN BUAH SERTA KADAR GULA BUAH TANAMAN MATOA MERAH (Pometia pinnata Forst) - Maruli Tua; Adiwirman; Herman (UIR Press, 2022)
Matoa fruit is one of the original Indonesian fruits from Papua. Matoa fruit is very popular for its delicious taste and unique fruit aromas such as durian and rambutan. many matoa plants can be found in Pekanbaru with age of 13, so it is necessary to conduct a research on the matoa fruit. The purpose of this study was to determine the maximum weight of fresh fruit and total dissolved solids in red matoa based on the age of fruit collection. The study was conducted with a descriptive analysis. Thirteen year old red matoa plants were studied at Purwo Farm Gardens, Jalan Sri Kurnia, Palas, Agrowisata Village, Rumbai District, Riau. The study was conducted during 4 months from April to July 2020. The results showed the maximum fresh weight of red matoa fruits at the age of fruit collection of 56 days after pollination (DAP). Total dissolved solids (TDS) in red matoa fruit was 56 DAP.